TI_GERICHTE 11.2015.106 vom 6. September 2017 , Ammontare della tassa di giustizia per la pubblicazione di testamenti - TI Tribunale d'appello (2017)
Ammontare della tassa di giustizia per la pubblicazione di testamenti